The perspective of Malay reserve land and native land in Malaysia / Noor Syazwani Ahmad Tajuddin - Ahmad Tajuddin, Noor Syazwani (2021)
Conflicts between Malay Reservation and Land Native Land have become more significant among the native peoples of the world. These conflicts in Malaysia, especially in Sabah, are becoming hottest issues because they include protection of indigenous land use rights, capital, customary traditions, cultural and traditional beliefs. The question of possession of Malay Reserve Land and Native Land occurs as the groups need to protect their claim to traditional or customary land. Customary communities long consider the land as a symbol of their existence’s identity. Nonetheless, the absence of municipal participation and a lack of policy accountability in land transactions have been a subject of contemporary controversy. To understand this conflict, the land title system and its implications, especially for indigenous communities, need to be looked into. The goal of this analysis is to define and explore the Malay Reserve Land legislation for Peninsular Malaysia and Native Land practices for Sabah, and to examine the process and procedure for enforcing ownership for Malay Reserve Land and Native Land. The approach for this research starts with the approach of planning which defines the field of analysis and the form of land management that will be studied. Next approach is to collect data. The scope of data collection in this research is indirect data comprising data from previous research reading content, conversation, interpretation and results.